What is the Difference between Online Learning and Traditional Teaching in Medical Education? - O. E. Osadchii (Кубанский научный медицинский вестник, 2020)
The online learning, which is now widely implemented owing to the constraints imposed by COVID-19 pandemic, offers many advantages when compared to the traditional teaching. The online teaching course is available to student any time and can be accessed from any location, providing there is a connection to the Internet, which allows remote learning at home using a fl exible and convenient study schedule that does not disturb other daily activities. The online course contains more informative learning materials, because the multimedia software enables to combine a variety of diverse elements within a given teaching unit, such as texts, PowerPoint presentations, computer animations, video clips, and audio fi les. The amount of time needed to go through the topics of the online course can be variable for different students, depending on their basic knowledge and motivation for learning, thus supporting more personalized learning experience. In contrast to the traditional teaching, that applies a teacher-centered approach, with online teaching the students become independent learners taking the main responsibility for the knowledge acquisition. Therefore, the students’ ability to succeed with online learning is critically determined by the self-discipline, rational time management skills, and monitoring the individual progress. While traditional teaching is largely based on passive learning through memorization of information by student, the online course offers multiple opportunities for self-directed, active learning, including questions for self-assessment, the web links to the relevant learning resources, and the interaction with peers using text messengers, discussion forums and web chats. The weak points of the online learning approach are that the self-studies are easy to procrastinate when the student is not strongly motivated to learn, and that it limits social contacts, leading to the feeling of isolation. Importantly, when developing the online learning course, the computer technology is supposed to be just a technical instrument, whereas the main emphasis is placed on the quality of teaching materials and their relevance to the objectives of the medical curriculum.